Hand sewing magic : essential know-how for hand stitching : with pro tips, tricks, and troubleshooting ; master tension and other techniques ; 10 easy, creative projects /: essential know-how for hand stitching : with pro tips, tricks, and troubleshooting ; master tension and other techniques ; 10 easy, creative projects. ([2019]) - Krawczyk, Lynn
No abstract available